Autophagy failure in Alzheimer's disease and the role of defective lysosomal acidification. Issue 12 (16th June 2013) - Wolfe, Devin M.; Lee, Ju‐hyun; Kumar, Asok; Lee, Sooyeon; Orenstein, Samantha J.; Nixon, Ralph A.
Abstract Autophagy is a lysosomal degradative process which recycles cellular waste and eliminates potentially toxic damaged organelles and protein aggregates. The important cytoprotective functions of autophagy are demonstrated by the diverse pathogenic consequences that may stem from autophagy dysregulation in a growing number of neurodegenerative disorders. In many of the diseases associated with autophagy anomalies, it is the final stage of autophagy–lysosomal degradation that is disrupted. In several disorders, including Alzheimer's disease (AD), defective lysosomal acidification contributes to this proteolytic failure. The complex regulation of lysosomal pH makes this process vulnerable to disruption by many factors, and reliable lysosomal pH measurements have become increasingly important in investigations of disease mechanisms. Although various reagents for pH quantification have been developed over several decades, they are not all equally well suited for measuring the pH of lysosomes. Here, we evaluate the most commonly used pH probes for sensitivity and localisation, and identify LysoSensor yellow/blue‐dextran, among currently used probes, as having the optimal profile of properties for measuring lysosomal pH. In addition, we review evidence that lysosomal acidification is defective in AD and extend our original findings, of elevated lysosomal pH in presenilin 1 (PS1)‐deficient blastocysts and neurons, to additional cell models of PS1 and PS1/2 deficiency, to fibroblasts from AD patients with PS1 mutations, and to neurons in the PS/APP mouse model of AD.